SECURITY AS A MODERATION OF INTEREST IN USING A DIGITAL WALLET WITH A TECHNOLOGY ACCEPTANCE MODEL (TAM) - Ratih Kusumastuti; Rudy Haryanto; Umi Hidayati; Teguh Setiawan Wibowo (Jurnal Ekonomi, 2023)
Technological advances have advanced rapidly and spread to all corners of the country. The use of digital wallets has become a very popular means of making payments online, the use of digital wallets has been specifically designed to benefit users in terms of convenience and ease of use. Now a person can make payments without having to meet in person because of the long distance from where he lives. This research was conducted to determine a person's interest in using a digital wallet technology system using the TAM (Technology Acceptance Model) theory developed by Davis in 1989 as a research model. The population and sample in this study are digital wallet users in Indonesia who were obtained using the probability sampling technique: simple random which was successfully obtained totaling 280 respondents in this study. Data analysis techniques using Smart PLS obtained from questionnaires. The results of the study found that perceived usefulness and perceived convenience partially had a significant effect. Meanwhile, security as a moderating variable is able to moderate the effect of perceived usefulness and perceived convenience on the interest in using digital wallets